The Option of an Oil Tax to Fund Transportation and Infrastructure - Crane, Keith (RAND Corporation, 2011)
Federal spending on surface-transportation infrastructure outpaces federal taxes on gasoline and diesel fuel. Increasing fuel efficiency means that fuel-purchase expenditures have dropped, so real revenue generated from these taxes has declined. A percentage tax on crude oil and imported refined-petroleum products consumed in the United States could fund U.S. transportation infrastructure.